2001
DOI: 10.1037/0735-7028.32.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Parents' attitudes toward their child's therapist and therapy.

Abstract: Parents of children in therapy typically have strong feelings and thoughts about their child's treatment, and their cooperation and support is often a critical aspect of successful treatment. Recent literature, in conjunction with the results of a small-scale study of 51 parents of children currently in treatment, suggests that contrary to classic psychoanalytic literature, parents experience primarily positive attitudes and feelings toward their child's therapist; they tend to feel hopeful, understood, and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
1
17
0
2
Order By: Relevance
“…This is problematic for parents of adolescents who have had few chances to voice their perceptions about the experience of family therapy (Breunlin, Breunlin, Kearns, & Russell, 1988; Kuehl, Newfield, & Joanning, 1990; Mann & Bordin, 1991). While some studies indicate that early termination of therapy is often the result of poor parent‐therapist relationship, it has also been found that parents of adolescents in therapy are supportive, respectful, and helpful partners in the therapeutic process (Kuehl et al., 1990; Nevas & Farber, 2001). Because of this, it seems clear that furthering our understanding of the experience of parents is essential and critical to therapeutic success.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This is problematic for parents of adolescents who have had few chances to voice their perceptions about the experience of family therapy (Breunlin, Breunlin, Kearns, & Russell, 1988; Kuehl, Newfield, & Joanning, 1990; Mann & Bordin, 1991). While some studies indicate that early termination of therapy is often the result of poor parent‐therapist relationship, it has also been found that parents of adolescents in therapy are supportive, respectful, and helpful partners in the therapeutic process (Kuehl et al., 1990; Nevas & Farber, 2001). Because of this, it seems clear that furthering our understanding of the experience of parents is essential and critical to therapeutic success.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…While family members’ experiences have been included in several studies, only a small number of studies have exclusively addressed the perceptions of parents of adolescents in family therapy (Kuehl et al., 1990; Nevas & Farber, 2001; Robbins et al., 2003). These studies indicate that parents of adolescents are generally pleased with family therapy—especially if they feel the therapist has a correct understanding of the presenting problem, demonstrates competence, and maintains a balanced alliance with both the parent and adolescent (Kuehl et al., 1990; Robbins et al., 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Consistent with the general treatment literature, the alliance has been found, predominantly in CBT studies, to predict proximal (e.g., change in cognitions) and distal (e.g., change in anxiety symptoms) outcomes in the treatment of multiple anxiety disorders (e.g., Casey, Oei, & Newcombe, 2005 ;Hayes, Hope, VanDyke, & Heimberg, 2007 ;Langhoff, Baer, Zubraegel, & Linden, 2008 ;Newman & Stiles, 2006 ;VanDyke, 2002 ;Vogel, Hansen, Stiles, & Gotestam, 2006 ) and youth anxiety disorders (e.g., Chiu, McLeod, Har, & Wood, 2009 ;Creed & Kendall, 2005 ;Hughes & Kendall, 2007 ;McLeod & Weisz, 2005 ) .…”
Section: Therapeutic Alliancementioning
confidence: 88%
“…Surprisingly little research has examined and demonstrated the relationship between therapist empathy and the therapeutic alliance in the treatment of anxiety disorders (e.g., DeGeorge, 2008 ) . However, indirect evidence in the form of the relationship between interpersonal skills relating to symptom improvement in anxiety disorders suggests that these skills help build the alliance with these patients (e.g., Keijsers, Schaap, Hoogduin, & Lammers, 1995 ;Newman & Stiles, 2006 ) . When using these skills, it is important that therapist provides an interest in the patient that is genuine, as clinician overemphasis on commonality with the patient can come across as inauthentic and has been found to negatively predict the therapeutic alliance (Creed & Kendall, 2005 ) .…”
Section: Approaches To Address Issues With Alliance Motivation and mentioning
confidence: 98%
“…Most contemporary therapists consider work with parents of children and adolescents to be a crucial part of the therapeutic enterprise (Nevas & Farber, 2001). However, the exact nature of this work is elusive.…”
Section: Self-disclosure With Parentsmentioning
confidence: 99%